The 1996-97 Gas Price Review in Argentina - Gomez-Labo, Andres; Foster, Vivien (World Bank, Washington, DC, 2012)
Argentina's natural gas industry was privatized at the end of 1992. Prior to divestiture, the state-owned monopoly Gas del Estado was divided into two transport and eight distribution companies, all of which were sold through international bidding. An independent government body, Ente Naal Regulador de Gas (Enargas), was established to regulate the transport and distribution segments of the industry. As part of its mandate, Enargas is in charge of price reviews. These reviews, which occur every five years, determine the allowed tariffs for each transport and distribution company. The first such review took place in 1996-97, and the new tariffs went into effect in January 1998. This Note examines the methodology and outcome of this experience. The Enargas price review is of interest for several reasons. First, it is the first of its kind in Argentina, and one of the first in a developing country. The outcome of the process provides a test of the regulatory framework adopted by the Argentine government, and may influence regulatory reform in other parts of the world. Second, as the first such event, the 1996-97 review set a precedent for methodologies and approaches to be used in future utility price reviews in Argentina. Finally, the approach used to calculate the cost of capital-as well as the other parameters used to set prices-provide an interesting illustration of how theoretical and practical methods from regulatory practice in industrial countries can be adapted to developing countries, where data availability and other restrictions prevent a direct transfer of techniques.